2022
DOI: 10.3897/pharmacia.69.e80261
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with clinical pharmacy services and the affecting factors: a literature review

Abstract: Service quality is measured to assess the consistency of medical services provided to fulfill patient expectations. This article provides an overview of patient satisfaction with clinical pharmacy services and the influencing factors. A literature search from MEDLINE and EBSCO databases was performed with the keywords “patient satisfaction”, “pharmacy service”, “hospital pharmacy service”, and “clinical pharmacy service”. The inclusion criteria for articles are original articles, full papers, articles in Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, it is entirely feasible to adapt such work to local systems. There is already an evidence base demonstrating that CPS are beneficial in multiple aspects such as optimized drug utilization and overall hospitalization costs ( McMullin et al, 1999 ; Reardon et al, 2015 ; Rychlickova et al, 2016 ), increased drug safety ( Anderson and Schumock, 2009 ; Simoens et al, 2011 ), improved medication adherence ( Schulz et al, 2019 ; McCarthy and Thomas Bateman, 2022 ), reduced hospital admissions ( Scullin et al, 2007 ; Gillespie et al, 2009 ), reduced length of hospital stay ( Scullin et al, 2007 ), reduced outpatient healthcare utilization and costs ( Byrne and Dalton, 2017 ), higher patient satisfaction ( Yuliandani et al, 2022 ) and positive feedback from other healthcare professionals ( Chevalier et al, 2016 ). Nevertheless, research on the theory and practice of CPS in CEE countries is still of value, as this may help to benchmark available solutions, prioritizing the best ones, and their wider implementation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is entirely feasible to adapt such work to local systems. There is already an evidence base demonstrating that CPS are beneficial in multiple aspects such as optimized drug utilization and overall hospitalization costs ( McMullin et al, 1999 ; Reardon et al, 2015 ; Rychlickova et al, 2016 ), increased drug safety ( Anderson and Schumock, 2009 ; Simoens et al, 2011 ), improved medication adherence ( Schulz et al, 2019 ; McCarthy and Thomas Bateman, 2022 ), reduced hospital admissions ( Scullin et al, 2007 ; Gillespie et al, 2009 ), reduced length of hospital stay ( Scullin et al, 2007 ), reduced outpatient healthcare utilization and costs ( Byrne and Dalton, 2017 ), higher patient satisfaction ( Yuliandani et al, 2022 ) and positive feedback from other healthcare professionals ( Chevalier et al, 2016 ). Nevertheless, research on the theory and practice of CPS in CEE countries is still of value, as this may help to benchmark available solutions, prioritizing the best ones, and their wider implementation.…”
Section: Discussionmentioning
confidence: 99%
“…However, future studies could develop a more standardized scale that measures travelers' satisfaction with pharmacy-managed travel services and comprehensively addresses all dimensions and aspects of the service. Several studies have also reported high patient satisfaction with pharmacist-delivered pharmaceutical care services [45][46][47][48][49]. In addition, a study by Ekenga et al from the US revealed that 91.8% of the public perceived community pharmacists as healthcare providers [50].…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22] Pharmacist-directed care has been shown to improve patients' quality of life and AEs, and improve patient satisfaction, care team member satisfaction, and adherence. [18][19][20][23][24][25][26][27] At The University of Texas MD Anderson Cancer Center, 11 clinical pharmacy specialists (CPSs) are dedicated to the GI medical oncology center and are credentialed for drug therapy management delegation under the physician staff. These CPSs hold certification in oncology through the Board of Pharmacy Specialists.…”
Section: Introductionmentioning
confidence: 99%